High Expression of Cancer-IgG Is Associated With Poor Prognosis and Radioresistance via PI3K/AKT/DNA-PKcs Pathway Regulation in Lung Adenocarcinoma - Yang, Xiongtao; Wang, Guohui; You, Jing; Gu, Runchuan; Xu, Xiaohong; Xu, Changdan; Wang, Hao; Zhao, Ruisong; Qiu, Xiaoyan; Zhu, Guangying (Frontiers in Oncology, 2021)
Background: Lung adenocarcinoma (LUAD) is the dominant type of lung neoplasms, and radiotherapy is its mainstay treatment, yet poor prognosis caused by radioresistance remains problematic. Cancer-derived immunoglobulin G (cancer-IgG) has been detected in multiple cancers and plays important roles in carcinogenesis. This study aimed to demonstrate that cancer-IgG is associated with poor prognosis of LUAD and to identify its role in radioresistance. Methods: Cancer-IgG expression was detected by immunohistochemistry from 56 patients with stage III LUAD and by western blot and immunofluorescence in LUAD cell lines and in a human bronchial epithelial cell line. The effects of cancer-IgG silencing on the proliferation and apoptosis of PC9 and H292 cells were evaluated by plate cloning and apoptosis assay; the effects of cancer-IgG silencing on DNA damage repair ability and radiosensitivity were evaluated by colony-forming assay, γH2AX immunofluorescence, and neutral comet assay. Finally, we used the protein phosphorylation microarray and western blot to explore mechanisms involving cancer-IgG that increased radioresistance. Results: Cancer-IgG is widely expressed in stage III LUAD, and the overall survival and disease-free survival of patients with positive expression are notably lower than those of patients with negative expression, indicating the associations between cancer-IgG and poor prognosis as well as radioresistance. The expression of cancer-IgG in the four LUAD cell lines was located mainly on the cell membrane and cytoplasm and not in the normal lung epithelial cell. Knockdown of cancer-IgG in PC9 and H292 cells resulted in increased apoptosis and negatively affected cancer cell proliferation. After irradiation, silencing of cancer-IgG showed a decrease in colonies as well as increases in the Olive tail moment and γH2AX foci in nucleus, indicating that the knockdown of cancer-IgG resulted in a decrease in the damage repair ability of DNA double-strand breaks in LUAD cells and an enhanced radiosensitivity. The expression of p-AKT, p-GSK3β, and p-DNA-PKcs decreased in the knockdown group after radiotherapy, suggesting that cancer-IgG could affect radiotherapy resistance by mediating double-strand breaks damage repair in LUAD cells through the PI3K/AKT/DNA-PKcs pathway. Conclusions: This study revealed that cancer-IgG regulates PI3K/AKT/DNA-PKcs signaling pathways to affect radioresistance of LUAD and associated with poor prognosis.